2022
DOI: 10.1142/s0217979222501776
|View full text |Cite
|
Sign up to set email alerts
|

Some optical soliton solutions to the generalized (1 + 1)-dimensional perturbed nonlinear Schrödinger equation using two analytical approaches

Abstract: In this paper, we study the perturbed nonlinear Schrödinger equation (P-NLSE) representing the propagation of waves and may be regarded as a nonlinear complicated physical model. We use the modified extended Tan hyperbolic function (METhF) approach and the [Formula: see text]-expansion approach to construct some new traveling wave structures. Several solutions have been found including dark soliton, periodic-type solitons, bell-shaped solitons, single bell-shaped solitons. We also show a graphical representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…This part's unique contribution to the research is demonstrated by a detailed contrast of the assessed findings with the previously calculated results. As the authors in [23], study the (1+1)-dimensional NLPSM, by using different analytical techniques to find exact solutions. Our inquiry synthesized this research to apply more effective techniques.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This part's unique contribution to the research is demonstrated by a detailed contrast of the assessed findings with the previously calculated results. As the authors in [23], study the (1+1)-dimensional NLPSM, by using different analytical techniques to find exact solutions. Our inquiry synthesized this research to apply more effective techniques.…”
Section: Resultsmentioning
confidence: 99%
“…They found that it would be possible to use the dark solitons to create long-lasting oscillations in the wave field, which might be useful for information processing and storage. The main objective of the article is to find the novel soliton solutions of the given below (1+1)-dimensional nonlinear perturbed Schrödinger model [23], by using a modified Sardar sub-equation approach.…”
Section: Introductionmentioning
confidence: 99%